2021
DOI: 10.15520/jcmro.v4i02.398
|View full text |Cite
|
Sign up to set email alerts
|

Are We Ready For Covid – 19 Vaccines? – A General Side Effects Overview

Abstract: A vaccine is considered to be one of the best options in public health safety, specifically when there is no effective vaccine available against that infectious disease.6 Classic vaccine development often takes years, but developing a vaccine for the prevention of Covid- 19 has turned out to be a race between viruses and humans, and along with the identification of other similar strains has made it more difficult. COVID- 19 has serious and life-threatening complications and no one knows how COVID- 19 is affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Respondents (75.53%) had post vaccination symptoms, commonest were the local pain at injection site (28.72%), fever (12.76%), Myalgia (12.77%), tiredness (8.51%) and Headache (5.32%). Jayadevan R [7] reported tiredness as most common symptom in 45% respondents, it followed by Myalgia (44%), Fever (34%) and headache (28%) and local pain at injection site by 27% of the respondents.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Respondents (75.53%) had post vaccination symptoms, commonest were the local pain at injection site (28.72%), fever (12.76%), Myalgia (12.77%), tiredness (8.51%) and Headache (5.32%). Jayadevan R [7] reported tiredness as most common symptom in 45% respondents, it followed by Myalgia (44%), Fever (34%) and headache (28%) and local pain at injection site by 27% of the respondents.…”
Section: Discussionmentioning
confidence: 97%
“…When compared the post vaccination symptoms with the type of vaccine used, Covishield had more vaccine related symptoms (79.76%) as compared to the Covaxin (50%) in our study. The study conducted by Jayadevan R [7] showed vaccine related symptoms i.e. 66% with Covishield, 53% with COVAXIN, 70.7% for PFIZER and 24.4% with Sinopharm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The novel coronavirus disease COVID-19 is a global health catastrophe [1], that has impacted public health, economies, and people's social interactions and daily lives worldwide [2]. It is a respiratory illness with a high infection rate [3], the possibility of infection from asymptomatic infection [4], and the ability to cause fatal complications.…”
Section: Introductionmentioning
confidence: 99%